IMPLEMENTATION OF A GENERAL INTEREST PRINCIPLE OF VILLAGE INFRASTRUCTURE DEVELOPMENT BASED ON ARTICLE 83 LAW NUMBER 6 OF 2014 ABOUT THE VILLAGE (Study of Bumi Agung Wates Village, Way Kanan District) - Anggalana; Irawan, Wayan Riki; Pratiwi, Ayang Widi; Rinanda, Diandra (Progressive Law Review, 2021)
The problem that exists in Bumi Agung Wates Village, Way Kanan Regency, is the unequal development of village infrastructure. This condition can be seen from the connecting road between Way Kanan Regency and East Ogan Komering Ulu Regency, precisely Bumi Agung Wates Village (BAW), Bahuga District, Way Kanan Regency, Lampung Province, with badly damaged conditions. The problem of this research is How is the implementation of the principle of orderly public interest in village infrastructure development based on Article 83 of Law Number 6 of 2014 concerning Villages (Study of Bumi Agung Wates Village Way Kanan District)? and What are the factors inhibiting the implementation of the principle of orderly public interest in the development of village infrastructure based on Article 83 of Law Number 6 of 2014 concerning Villages (Study of Bumi Agung Wates Village Way Kanan District)? The research method uses a normative and empirical juridical approach. The type of data used is secondary data and primary data. Collecting data through library research and field research. Analysis of the data used is qualitative juridical. Based on the results of the study it was concluded that the implementation of the principle of orderly public interest in the development of village infrastructure based on Article 83 of Law Number 6 of 2014 concerning Villages, had not been implemented to the fullest because development in the village of Bumi Agung Wates Way Kanan Regency was only a road in an alley or small road; while the main road has not been developed at all, while the main road is widely used by the community or farmers to transport crops to be brought to the city. The inhibiting factors for the implementation of the principle of order of public interest in the development of village infrastructure based on Article 83 of Law Number 6 of 2014 concerning Villages are among others the relatively low level of community education and facilities and infrastructure in the form of community work equipment that does not support until the end of physical implementation. As a suggestion from the author, the Way Kanan Regency Government should be able to resolve the problem or the inhibiting factor of the implementation of the principle of public order in the development of village infrastructure based on Article 83 of Law Number 6 of 2014 concerning Villages in Bumi Agung Wates Village, Bahuga District, Way Kanan Regency. The government of Bumi Agung Wates Village, Bahuga Subdistrict, Way Kanan Regency,